How lactate affects immune strategies in lymphoma - Zhou, Yuehan; Lou, Jinzhan; Tian, Yuqin; Ding, Jinlei; Wang, Xiaobo; Tang, Bo (Frontiers in Molecular Biosciences, 2024)
Tumor cells undergo metabolic reprogramming through shared pathways, resulting in a hypoxic, acidic, and highly permeable internal tumor microenvironment (TME). Lactate, once only regarded as a waste product of glycolysis, has an inseparable dual role with tumor immunity. It can not only provide a carbon source for immune cells to enhance immunity but also help the immune escape through a variety of ways. Lymphoma also depends on the proliferation signal of TME. This review focuses on the dynamic process of lactate metabolism and immune function changes in lymphoma and aims to comprehensively summarize and explore which genes, transcription factors, and pathways affect the biological changes and functions of immune cells. To deeply understand the complex and multifaceted role of lactate metabolism and immunity in lymphoma, the combination of lactate targeted therapy and classical immunotherapy will be a promising development direction in the future.